Genetic diversity of Helicobactor pylori isolates through Microevolution in vivo - Carroll, Ian M. (Trinity College (Dublin, Ireland). Department of Microbiology, 2004)
Chronic infection with H. pylori causes peptic ulcer disease and its presence is strongly linked with gastric adenocarcinoma and mucosa-associated lymphoid tissue (MALT) lymphoma. One of the most interesting characteristics of H. pylori is its genetic diversity. This organism has been shown to have a panmicitic or freely recombining population structure. Indeed, unrelated clinical H. pylori isolates display disparate DNA fingerprints. The genetic diversity of H. pylori isolates has been shown to vary within different parts of the world. Moreover, recent studies have demonstrated geographical partitioning of H. pylori isolates and have detected the presence of weakly clonal groupings. In addition, a lack of diversity has been demonstrated between the two fully genome-sequenced H. pylori strains (26695 and J99). Thus, the extent of genetic diversity within the H. pylori population structure may have been overstated. The present study aimed to characterise the population structure of clinical Irish H. pylori isolates and compare this structure with those of different geographical regions.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin